2017
DOI: 10.1007/s11738-017-2434-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of low-molecular weight organic acids synthesized by Salix growing in soils characterized by different Cu, Pb and Zn concentrations

Abstract: The aim of the study was to evaluate the biosynthesis and exudation of 10 low-molecular weight organic acids (LMWOAs) into the rhizosphere with a simultaneous analysis of the acid contents in the roots and leaves of 9 Salix taxa growing on two experimental areas, differing in their concentrations of copper (Cu), lead (Pb) and zinc (Zn) in the soil (Area 1-low, Area 2-high concentration). The obtained results reveal a significant difference in the phytoextraction of the tested Salix taxa for the analysed metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 52 publications
3
13
1
Order By: Relevance
“…Oxalic acid is one of the most important secondary metabolites in plants under adverse stress conditions, it can stimulate peroxidase activity and improves the antioxidant capacity [33]. Herein, the concentrations of oxalic acid in the roots of T. distichum and S. matsudana were greatly affected by the experimental period but not significantly affected by different flooding treatments.…”
Section: Discussionmentioning
confidence: 83%
“…Oxalic acid is one of the most important secondary metabolites in plants under adverse stress conditions, it can stimulate peroxidase activity and improves the antioxidant capacity [33]. Herein, the concentrations of oxalic acid in the roots of T. distichum and S. matsudana were greatly affected by the experimental period but not significantly affected by different flooding treatments.…”
Section: Discussionmentioning
confidence: 83%
“…Samples of P. sylvestris L. roots and needles (~ 1.0 g), ground to powder in a mortar chilled using liquid nitrogen were collected in 50 mL centrifuge tubes and stored frozen (− 80 °C) until analysis. The extraction method for ALMWOAs and phenolic compounds analysis in all the studied matrices was presented in detail by Magdziak et al (2017) and Gąsecka et al (2017). The obtained solutions were evaporated to dryness and stored frozen (− 80 °C) until analysis.…”
Section: Preparation Of Rhizosphere Roots and Needle Samples Of P Sylvestris L For Almwoas And Phenolic Compound Analysismentioning
confidence: 99%
“…sorption and desorption (Wang et al 2015), oxidation and reduction (Blaylock and James 1994) and precipitation and dissolution (Zhou et al 2007). Moreover, in some of the previously mentioned studies, ALMWOAs and phenolic compounds have been found in plant tissues (mainly, roots and leaves) (Drzewiecka et al 2017;Magdziak et al 2017), where next to the rhizosphere, plants use ALMWOAs to transport, sequestrate and prevent cytoplasmic precipitation of toxic elements in cells, or in the case of phenolic compounds, in participation in adaptation and detoxification mechanisms mainly related to their structure and antioxidant properties (Ivanov et al 2012;Jiang et al 2017a, b;Benbettaieb et al 2018).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, with the addition of DTPA, the accumulation of Tl in barley was enhanced markedly [26]. Salix taxa performs at a higher extraction efficiency of heavy metals from Cu, Pb, and Zn contaminated soil, which is mainly related to the rhizosphere secreting more small molecular organic acids, such as oxalic acid and malic acid [27]. The bioavailability of heavy metals reached the maximum at the second day after the addition of the chelating agent, EDTA (ethylene diamine tetraacetic acid), and its combination with small molecular organic acids (citric acid and oxalic acid) could significantly improve the extraction efficiencies of Cd and Zn.…”
Section: Introductionmentioning
confidence: 99%